Keanekaragaman Tumbuhan yang Berpotensi sebagai Bahan Pangan di Hutan Lindung Pulau Panjang Jepara Jawa Tengah - Utami, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Panjang Isaland is small island in Jepara, Central Java province, with covers about 19,73 ha areas but information on plant biodiversity especially, which has potency as source of foodstuff is still limited. For that reason a plant exploration and inventory in this area has been done in forest protected Panjang Island. Nineteen species of edible plant have been recorded, and they consist of fruits (6 species), vegetables (7 species) and tuber (6 species). Of these species have not all used by local communities to fulfill their food needs. Need to be introduced to local communities the potentialÂ of edible plants Â in Panjang Island in order to support the efforts of food independence in Indonesia.